A novel lateral cavity surface emitting laser with top sub-wavelength grating. (1st January 2015) - Qi, Aiyi; Wang, Yufei; Guo, Xiaojie; Zheng, Wanhua
Abstract We report a novel lateral cavity surface emitting laser based on sub-wavelength high-index-contrast grating with in-plane resonance and surface-normal emission. The device is fabricated on a simple commercial wafer without the distributed Bragg reflector and it needs no wafer bonding. It exhibits a side mode suppression ratio of 23.0 dB and a high output power of 5.32 mW at 1552.44 nm. The specific single mode lasing agrees well with the band edge mode calculation of the grating. In 3D simulation, we observe obvious light output from the grating.